PENGARUH BAURAN PEMASARAN TERHADAP PENJUALAN PRODUK PADA BAZAAR KEWIRAUSAHAAN DI UNIVERSITAS PELITA BANGSA - Abdy Kurniawan Chairul; Azi Matur Rahmi; Silvia Novi Yanti (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the influence of the marketing mix on product sales in an entrepreneurial bazaar at Pelita Bangsa University. The marketing mix studied includes product, price, promotion, and place. The research method used is a quantitative method with a survey approach. Data were obtained by distributing questionnaires to student entrepreneurs who participated in the entrepreneurial bazaar. Data analysis techniques used validity tests, reliability tests, multiple linear regression analysis, t-tests, F-tests, and coefficients of determination. The results of the study indicate that the marketing mix simultaneously has a significant effect on product sales in an entrepreneurial bazaar. Partially, product and promotion variables have the most dominant influence on increasing sales, while price and place also have a positive influence on consumer purchasing decisions. The coefficient of determination value indicates that the marketing mix variables are able to explain most of the variation in product sales. Thus, the implementation of an appropriate marketing mix strategy can increase sales and competitiveness of student products in entrepreneurial bazaar activities.